Pediatric Emergency Department Responses to COVID-19: Transitioning From Surge Preparation to Regional Support. (18th February 2021) - Hartford, Emily A.; Keilman, Ashley; Yoshida, Hiromi; Migita, Russell; Chang, Todd; Enriquez, Brianna; Liu, Deborah R.
ABSTRACT: In the midst of a global pandemic, hospitals around the world are working to meet the demand for patients ill with the 2019 coronavirus disease (COVID-19) caused by the novel coronavirus first identified in Wuhan, China. As the crisis unfolds, several countries have reported lower numbers as well as less morbidity and mortality for pediatric patients. Thus, pediatric centers find themselves pivoting from preparing for a patient surge to finding ways to support the regional response for adults. This study describes the response from 2 West Coast freestanding academic children's hospitals that were among the first cities in the United States impacted during this pandemic.